Access to free or low-cost tuberculosis treatment for migrants and refugees along the Thailand-Myanmar border in Tak province, Thailand - Tschirhart, Naomi (Int J Equity Health, 2016)
BACKGROUND: In Tak province, Thailand migrants and refugees from Myanmar navigate a pluralistic healthcare system to seek Tuberculosis (TB) care from a variety of government and non-governmental providers. This multi-methods qualitative study examined access to TB, TB/HIV and multidrug-resistant tuberculosis (MDR-TB) treatment with an emphasis on barriers to care and enabling factors. METHODS: In the summer and fall of 2014, we conducted 12 key informant interviews with public health officials and TB treatment providers. We also conducted 11 focus group discussions with migrants and refugees who were receiving TB, TB/HIV and MDR-TB treatment in Tak province as well as non-TB patients. We analyzed these data through thematic analysis using both predetermined and emergent codes. As a second step in the qualitative analysis, we explored the barriers and enabling factors separately for migrants and refugees. RESULTS: We found that refugees face fewer barriers to accessing TB treatment than migrants. For both migrants and refugees, legal status plays an important intermediary role in influencing the population’s ability to access care and eligibility for treatment. Our results suggest that there is a large geographical catchment area for migrants who seek TB treatment in Tak province that extends beyond provincial boundaries. Migrant participants described their ability to seek care as linked to the financial and non-financial resources required to travel and undergo treatment. Patients identified language of health services, availability of free or low cost services, and psychosocial support as important health system characteristics that affect accessibility. CONCLUSION: Access to TB treatment for migrants and refugees occurs at the interface of health system accessibility, population ability and legal status. In Tak province, migrant patients draw upon their social networks and financial resources to navigate a pathway to treatment. We revised a conceptual framework for access to healthcare to incorporate legal status and the cyclical pathways through which migrants access TB treatment in this region. We recommend that organizations continue to collaborate to provide supportive services that help migrants to access and continue TB treatment.